Punishment and medieval education - Parsons, Ben (D.S. Brewer, 2018)
What meanys shall I use to lurne withoute betynge?", asks a pupil in a translation exercise compiled at Oxford in 1460s. One of the most conspicuous features of medieval education is its reliance on flogging. Throughout the period, the rod looms large in literary and artistic depictions of the schoolroom: it appears in teaching manuals, classroom exercises, and even in the iconography of instruction, which invariably personifies Grammatica as a woman brandishing a birch or ferule. However, as this book seeks to demonstrate, the association between teaching and beating was more than simply conventional. Medieval pedagogues and theorists did not merely accept the utility of punishment without question, but engaged with the issue in depth and detail. Almost every conceivable aspect of discipline was subject to intense scrutiny: the benefits it might transmit to learners, the relationship between mental development and physical correction, and the optimal ways in which chastisement should be performed, were all carefully examined. This book unpicks the various levels of this debate. It surveys material from multiple languages and discourses, in order to build up the fullest possible picture of medieval thought and practice. Each chapter addresses a specific aspect of punishment in school: topics include the classical inheritance of medieval teaching, the rituals and structures of discipline, theoretical accounts of its effects, and the responses of students themselves to grammar's regimen